The effect of the introduction of a standard monitoring protocol on the investigations performed on the metabolic control of type 2 diabetes at Addington Hospital Medical Outpatients Department, Durban, South Africa - J.M. Gill; A. Ross; F. Pirie; T. Esterhuizen (South African Family Practice)
Background: A comprehensive approach to the control of type 2 diabetes is required to reduce mortality and morbidity. To improve diabetes management, in 2005 a protocol for the monitoring and management of type 2 diabetes, aligned to the 2003 Society for Endocrinology, Metabolism and Diabetes of South Africa (SEMDSA) guidelines, was introduced at Addington Hospital Medical Outpatients Department, Durban, South Africa.